Organophosphorus Inhibition and Characterization of Recombinant Guinea Pig Acetylcholinesterase - D. Ruark, Christopher; R. Chapleau, Richard; A. Mahle, Deirdre; M. Gearhart, Jeffery (Protein and Peptide Letters, 2015)
Organophosphorus (OP) pesticides and nerve agents have been designed to inhibit the hydrolysis of the neurotransmitter acetylcholine by covalently binding to the active site serine of acetylcholinesterase while Alzheimer drugs and prophylactics, such as tacrine, are characterized by reversible binding. Historically, the guinea pig has been believed to be the best non-primate model for OP toxicology and medical countermeasure development because, similarly to humans, guinea pigs have low amounts of circulating OP metabolizing carboxylesterase. To explore the hypothesis that guinea pigs are the appropriate responder species for OP toxicology and medical countermeasure development, guinea pig acetylcholinesterase (gpAChE) was cloned into pENTR/D-TOPO, recombined into pT-Rex-DEST30 and expressed in Human Embryonic Kidney 293 cells. Recombinant gpAChE was purified to a specific activity of 800 U/mg using size exclusion and immobilized nickel affinity chromatography, with purity confirmed by gel electrophoresis. Ellman’s assay was used to enzymatically characterize gpAChE, identifying a KM of 154±18.7 µmol L-1 and a kcat of 4.79x104±5.26x102 /sec. Apparent gpAChE IC50’s for diisopropylfluorophosphate, dicrotophos, paraoxon, and an Alzheimer’s drug, tacrine, were found to be 10.1±1.98, 337±108, 1.02±0.29 and 0.30±0.01 µmol L-1, respectively. Apparent gpAChE inhibition constants for diisopropylfluorophosphate, dicrotophos, paraoxon, and tacrine were found to be 8.40±0.60, 4.50±0.30, 0.29±0.01 and 0.42±0.07 µmol L-1, respectively. Lineweaver-Burk plots confirmed tacrine as a mixed inhibitor and paraoxon, dicrotophos and diisopropylfluorophosphate as irreversible non-competitive inhibitors. gpAChE bimolecular rate constants for diisopropylfluorophosphate, dicrotophos and paraoxon were found to be 1.44±0.33x104, 1.56±0.12x103 and 4.57± 0.23x105 L µmol-1 min-1, respectively. Although the blood levels of OP metabolizing carboxylesterases in the guinea pig are similar to the low levels in human blood, the gpAChE is different in its enzymology. Therefore, medical countermeasures against OP intoxication should be tested for efficacy with the recombinant form of gpAChE prior to initiating animal studies.
Keywords: organophosphorus